Designing a didactic sequence for teaching astronomy and english through games to develop the oral skills of children of fourth grade from a public school in Pereira (2022)
The present project aims to design a Didactic Sequence for teaching English and astronomy through games to fourth-grade learners of a public school in the city of Pereira. Due to globalization, the necessity of being able to communicate with people around the world has increased. Colombia is one of the countries that have found the necessity of training competitive English language speakers since it has become the lingua franca for businesses, knowledge, and cultural interchanges. For those reasons, the Colombian educational system has created different bilingualism policies to train competitive bilingual speakers; however, the results that Colombia has obtained in international and national tests have demonstrated that the process has not been successful. Bearing this in mind, it is necessary to implement a methodology that helps to reinforce the English abilities in which students are failing. This project proposes the DS as a methodology for teaching the English language mainly focusing on the development of the students’ speaking productive skills; in addition, due to the flexibility of this methodology for the implementation of topics and activities, this didactic sequence implements astronomy as the main theme. Generating in students’ abilities such as critical thinking, spatial intelligence, inquiry, and research abilities; moreover, students increased their English language skills in a safe environment.